Peningkatan Produktivitas Serbuk Jahe Instan Dengan Metode Mesin Parut Listrik Pada Kelompok Tani Kelurahan Bungus Barat Kota Padang - Rosiana Rizal; Helmice Afriyeni; Islahuddin Islahuddin; Sefrianita Kamal; Sara Surya (Jurnal Pengabdian Masyarakat Dharma Andalas, 2023)
This Community Service activity aims to provide information about ginger plants that have the best quality that can be processed into instant ginger powder, a method that can increase the productivity of instant ginger powder. This community service activity in alam mintanak farmer group, West Bungus sub-district, Padang city was carried out in 3 stages for 1 month. From the beginning of March to the 2nd week of May 2022, the preparation stage which consisted of meetings with related parties, preparation of proposals, and surveys were carried out. The next stage is Implementation which is the main agenda, including counseling and how to choose quality ginger plants and how to process ginger into instant ginger powder. The last stage is reporting as outlined in the form of this Community Service Journal. From this service activity, it is hoped that the people of Bungus Barat sub-district, Padang city will receive education on processing ginger into instant ginger powder and how to increase productivity.